(untitled) (Academicia Globe: Inderscience Research, 2023)
Infectious diseases are disorders caused by pathogenic microorganisms (e.g., bacteria, viruses, fungi, parasites) that may be transmitted directly or indirectly by various sources. Some infections may be harmful, but some may be harmless; all may be preventable. Certain patient populations may also be more susceptible to infections, including pregnant women.